Pharmacotherapy in COVID-19 patients: a review of ACE2-raising drugs and their clinical safety - Akhtar, Saghir; Benter, Ibrahim F.; Danjuma, Mohammed, I; Doi, Suhail A. R.; Hasan, Syed S.; Habib, Abdella M. (Taylor & Francis Ltd, 2020)
The COVID-19 pandemic is caused by the severe acute-respiratory-syndrome-coronavirus-2 that uses ACE2 as its receptor. Drugs that raise serum/tissue ACE2 levels include ACE inhibitors (ACEIs) and angiotensin-II receptor blockers (ARBs) that are commonly used in patients with hypertension, cardiovascular disease and/or diabetes. These comorbidities have adverse outcomes in COVID-19 patients that might result from pharmacotherapy. Increasing ACE2 could potentially increase the risk of infection, severity or mortality in COVID-19 or it might be protective as it forms angiotensin-(1-7) which exhibits anti-inflammatory/anti-oxidative effects and prevents diabetes- and/or hypertension-induced end-organ damage. Thus, there existed clinical uncertainty. Here, we review studies implicating 15 classes of drugs in increasing ACE2 levelsin vivoand the available literature on the clinical safety of these drugs in COVID-19 patients. Further, in a re-analysis of clinical data from a meta-analysis of 9 studies, we show that ACEIs/ARBs usage was not associated with an increased risk of all-cause mortality. Literature suggests that ACEIs/ARBs usage generally appears to be clinically safe though their use in severe COVID-19 patients might increase the risk of acute renal injury. For definitive clarity, further clinical and mechanistic studies are needed in assessing the safety of all classes of ACE2 raising medications.
Keywords: ACE inhibitors; angiotensin receptor blockers; RAAS; ACE2; Ang-(1-7); statins; COVID-19; Mineralocorticoid receptor inhibitors; GLP-1 agonists; DPP-4 inhibitors